The Effect of Capital Structure on Company Value in Automotive and Component Sector Companies in Go Public Period 2015 - 2019 - Gandy Ardiansa; Wiyono Wiyono; Fika Fitriasari (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This study aims to analyze the capital structure, firm value in the go public automotive and component sectors as well as the effect of capital structure on firm value. The analysis technique used is simple regression analysis with the SPSS program. The sample used is 9 companies taken using the purposive sampling method. The Independent variable is proxied by DER (Debt to Equity Ratio) and PBV (Price to Book Ratio). The results of the analysis show that the variables of capital structure and firm value have a significant negative effect. This means that a decrease in the capital structure will increase firm value.